Accumulation of Pericardial Fat Is Associated With Alterations in Heart Rate Variability Patterns in Hypercholesterolemic Pigs. (April 2020) - Uceda, Domingo E.; Zhu, Xiang-Yang; Woollard, John R.; Ferguson, Christopher M.; Patras, Ioannis; Carlson, Daniel F.; Asirvatham, Samuel J.; Lerman, Amir; Lerman, Lilach O.
Abstract : Background: Heart rate variability (HRV) and pulse rate variability are indices of autonomic cardiac modulation. Increased pericardial fat is associated with worse cardiovascular outcomes. We hypothesized that progressive increases in pericardial fat volume and inflammation prospectively dampen HRV in hypercholesterolemic pigs. Methods: WT (wild type) or PCSK9 (proprotein convertase subtilisin-like/kexin type-9) gain-of-function Ossabaw mini-pigs were studied in vivo before and after 3 and 6 months of a normal diet (WT-normal diet, n=4; PCSK9-normal diet, n=6) or high-fat diet (HFD; WT-HFD, n=3; PCSK9-HFD, n=6). The arterial pulse waveform was obtained from an arterial telemetry transmitter to analyze HRV indices, including SD (SD of all pulse-to-pulse intervals over a single 5-minute period), root mean square of successive differences, proportion >50 ms of normal-to-normal R-R intervals, and the calculated ratio of low-to-high frequency distributions (low-frequency power/high-frequency power). Pericardial fat volumes were evaluated using multidetector computed tomography and its inflammation by gene expression of TNF (tumor necrosis factor)-α. Plasma lipid panel and norepinephrine level were also measured. Results: At diet completion, hypercholesterolemic PCSK9-HFD had significantly ( P <0.05 versus baseline) depressed HRV (SD of all pulse-to-pulse intervals over a single 5-minute period, root mean square of successive differences, proportion >50 ms, high-frequency power, low-frequency power), and both HFD groups had higher sympathovagal balance (SD of all pulse-to-pulse intervals over a single 5-minute period/root mean square of successive differences, low-frequency power/high-frequency power) compared with normal diet. Pericardial fat volumes and LDL (low-density lipoprotein) cholesterol concentrations correlated inversely with HRV and directly with sympathovagal balance, while sympathovagal balance correlated directly with plasma norepinephrine. Pericardial fat TNF-α expression was upregulated in PCSK9-HFD, colocalized with nerve fibers, and correlated inversely with root mean square of successive differences and proportion >50 ms. Conclusions: Progressive pericardial fat expansion and inflammation are associated with a fall in HRV in Ossabaw mini-pigs, implying aggravated autonomic imbalance. Hence, pericardial fat accumulation is associated with alterations in HRV and the autonomic nervous system.